What Comes after: Disruption and Care in Health Science Librarianship. Issue 2 (3rd July 2021) - Lockmiller, Mary Catherine
Abstract: As a university health science librarian at a public institution, I witnessed much of this past year from the sidelines, locked in my home, and communicating almost entirely through a computer screen. Although the transition to at-home work was disruptive, it was only a single source of disruption among many: the pandemic itself, healthcare systems, misinformation, political turmoil, and extreme weather conditions. At the same time, I was faced with the constant pressure to "disrupt" my own work by finding new pathways for students and employees to access health science information, new sources of money flowing into the institution, and new methods to helping people make sense of the information sources we already provide. In this column, I want to make sense of these many disruptions and how the interplay between them is indicative of a wider cultural emphasis on pressuring library workers to achieve greater success with increasingly fewer resources. I begin with an introduction to complex systems theory as a means of making sense of disruption. Second, I establish the different ways that disruption affects those of us working with health science e-resources. Finally, I consider how organizational pressure to achieve greater success is antithetical to self-nurture, and how we can develop new avenues of resistance to preserve and care for ourselves and those around us.